Conservation-Compatible Oil Palm Development: Integrating High Conservation Value (HCV) Safeguards in Mandailing Natal, Indonesia - Bambang Tri Sasongko Adi; Surahman Putra; Ratna Kusuma Sari; Bonie Dewantara; Puspita Suryaningtyas (Green Publisher Indonesia, 2025)
The global palm oil industry faces increasing pressure to eliminate deforestation from its supply chains, driven by international commitments such as the European Union Deforestation Regulation (EUDR), Roundtable on Sustainable Palm Oil (RSPO) standards, and Indonesia’s Forest and Other Land Use (FOLU) Net Sink 2030 commitment. These frameworks require effective mechanisms to identify and safeguard ecologically and socially valuable landscapes within agricultural frontiers. Integrating High Conservation Value (HCV) principles into land use planning is therefore critical to balancing commodity production, biodiversity conservation, and community rights. This study analyzes how oil palm development in Mandailing Natal, North Sumatra, can align with High Conservation Value (HCV) protection. Using a 2024 district-wide ABKT-HCS (High Conservation Value and High Carbon Stock) assessment and scenario modeling, the study examines forest encroachment, institutional fragmentation, and policy gaps undermining sustainable land use. Although more than half of the district is legally defined as forest, rapid plantation expansion—driven by smallholder pressures, tenure insecurity, and weak inter-agency coordination—continues to erode ecological integrity and cultural landscapes. Scenario analysis shows that improving yields through Good Agricultural Practices (GAP) and participatory zoning can enhance productivity without new deforestation. The paper recommends integrating ABKT spatial data into formal land-use planning, institutionalizing Free, Prior, and Informed Consent (FPIC), and implementing community-based monitoring. These strategies support a jurisdictional sustainability transition consistent with Indonesia’s FOLU Net Sink 2030 objective.